2019
DOI: 10.1111/aor.13441
|View full text |Cite
|
Sign up to set email alerts
|

Single versus multi‐drug antimicrobial surgical infection prophylaxis for left ventricular assist devices: A systematic review and meta‐analysis

Abstract: Infection remains the Achilles heel of left ventricular assist device (LVAD) therapy. However, an optimal antimicrobial surgical infection prophylaxis (SIP) regimen has not been established. This study evaluated the efficacy of a single‐drug SIP compared to a multi‐drug SIP on clinical outcomes in patients undergoing continuous‐flow LVAD (CF‐LVAD) and pulsatile LVAD (P‐LVAD) implantation. An electronic search was performed to identify studies in the English literature on SIP regimens in patients undergoing LVA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
3
3
0
Order By: Relevance
“…A meta‐analysis by Patel and colleagues evaluated 14 studies which included 1311 patients to compare the effectiveness on clinical outcomes between a single‐drug SIP, defined as use of vancomycin, cefazlin or combinations of either versus a multi‐drug SIP, which was defined as the addition of other antimicrobial agents to the single‐drug regimen. The study found no significant difference in incidence of LVAD‐specific infections between the groups; however, a significantly lower survival rate was seen in patients who received multidrug SIP 12 . These findings, along with the findings of our study, suggest there is no advantage to multidrug regimens in comparison to a narrow SIP regimen.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…A meta‐analysis by Patel and colleagues evaluated 14 studies which included 1311 patients to compare the effectiveness on clinical outcomes between a single‐drug SIP, defined as use of vancomycin, cefazlin or combinations of either versus a multi‐drug SIP, which was defined as the addition of other antimicrobial agents to the single‐drug regimen. The study found no significant difference in incidence of LVAD‐specific infections between the groups; however, a significantly lower survival rate was seen in patients who received multidrug SIP 12 . These findings, along with the findings of our study, suggest there is no advantage to multidrug regimens in comparison to a narrow SIP regimen.…”
Section: Discussionsupporting
confidence: 59%
“…The study found no significant difference in incidence of LVAD-specific infections between the groups; however, a significantly lower survival rate was seen in patients who received multidrug SIP. 12 These findings, along with the findings of our study, suggest there is no advantage to multidrug regimens in comparison to a narrow SIP regimen.…”
Section: Allergy 1supporting
confidence: 68%
“…These findings support that for uncomplicated cases, broad spectrum antimicrobial coverage does not impact outcomes 13 . Similarly, a meta‐analysis involving 14 studies comparing the efficacy of a single‐drug SIP to a multi‐drug SIP in patients undergoing LVAD implantation found no significant difference in the overall incidence of LVAD‐specific infections 14 . Both aforementioned studies demonstrated no survival advantage of a multi‐drug SIP regimen over a single‐drug regimen at both 90 days and 1‐year post device implantation.…”
Section: Commentsupporting
confidence: 62%
“…One recent meta-analysis found no difference in rates of LVAD-specific infections when institutions used multidrug compared with single-drug surgical infection prophylaxis, highlighting the need for further insight into optimal perioperative protocols. 19 Interestingly, we observed higher frequencies of MDRO colonization and lower frequencies of VAD infections in VADs implanted before the June 2013 transition from vancomycin, levofloxacin, rifampin, and fluconazole perioperative antimicrobial prophylaxis to vancomycin and cefuroxime, possibly reflective of the broader spectrum antibiotic use in the earlier cohort.…”
Section: Discussionmentioning
confidence: 65%